Malaysia halal traceability and verification system using QR code - Thanin, Khairunnisa; Mashohor, Syamsiah; Wan Adnan, Wan Azizun (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Halal food traceability has less involvement from each level of operations in entire Halal food supply chain. Furthermore, verifying Halal logo still facing some problems because it is easy to be photocopied and imitated. Existing services such as SMS JAKIM, Halal Directory and barcode scanning are very high in cost and less performance. In this paper, a new approach of Mobile Halal Traceability and Verification system using QR code technology is developed using android development tool (ADT) and ZXing library. The objectives are to develop two modules which are traceability system and verification system to scan Halal meat product QR code using smartphone. Two-hundred Halal product databases and twenty cattle entrepreneurs’ contacts information were collected. The prototype system was tested in real-time to one hundred of respondents and an interview was conducted to both respondents and cattle entrepreneurs. For traceability system, 83 percents of farm have internet connectivity. However, 33 percent of entrepreneurs are still using paper-based documentation to record the livestock. The proposed traceability system only takes 4 seconds to record 30 livestock or products. For verification system, 95 percent of respondents found that this proposed system takes short time to response and 72 percent of respondents are very satisfied with the application. It is shows that the proposed system is usable and convenient in order to verify Halal meat product. The verification system also gives 100 percent data reliability compared to MyJakim Halal Directory on smartphone where user needs to type-in search keyword. In test-bed experiment, the system takes 1.23 seconds to complete the operations until results obtained. In order to secure the QR code, data encryption technique was implemented to the Halal meat product information. However, it is not impacting the performance of verification system where it only takes 1.63 seconds to get the results.